Assistance and Empowerment of Farmer Community in Past Eisesldp Project (A Case Study in Seven Districts in Southern Sulawesi, Gorontalo, and Northern Sulawesi Province) - A Saleh (Faculty of Animal Science, Bogor Agricultural University, 2003)
Assistance and empowerment of farmer community in past eisesldp project (A case study in seven districts in southern Sulawesi, Gorontalo, and Northern Sulawesi province)